2013
DOI: 10.1088/0953-2048/26/3/032001
|View full text |Cite
|
Sign up to set email alerts
|

Trapped fields up to 2 T in a 12 mm square stack of commercial superconducting tape using pulsed field magnetization

Abstract: The ability of superconductors to sustain persistent currents has been well exploited with (RE)BCO superconducting bulks, which can be magnetized to form a compact source of high magnetic field. However, thin films can also sustain persistent currents, which can be utilized by stacking them in layers to create a type of composite bulk. Such a stack is capable of trapping higher fields than a bulk, as reported in this paper. 12 mm wide, 55 µm thick commercial (RE)BCO tape from Superpower Inc was cut into 12 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 25 publications
2
46
0
2
Order By: Relevance
“…We performed comparison of the calculated distributions of the magnetic flux trapped by the stacks with the experimental dependences of Hall magnetometry measurements. Scanning height was 0.7 mm [3]. The calculated data are in consistence with the experimental data for the samples of circular shape (Figure 4 (a)) and the square shape (Figure 4,(b)).…”
Section: Resultssupporting
confidence: 78%
“…We performed comparison of the calculated distributions of the magnetic flux trapped by the stacks with the experimental dependences of Hall magnetometry measurements. Scanning height was 0.7 mm [3]. The calculated data are in consistence with the experimental data for the samples of circular shape (Figure 4 (a)) and the square shape (Figure 4,(b)).…”
Section: Resultssupporting
confidence: 78%
“…For both applications, it is crucial and significant to study the vortex shaking effect of superconducting stacks made of REBCO. REBCO stacks have been reported trapped magnetic field higher than 7 T at 4.2 K [1,2], making them promising candidate for high power density rotating machines. In the operation of rotating machines, the superconducting stacks are subjected to alternating external magnetic field, which may lead to the decay of the trapped magnetic field and results in lower performance of the machines.…”
Section: Introductionmentioning
confidence: 99%
“…By using second generation (2G)-HTS tapes, recently, Patel et al have reported a series of field cooling magnetization experiments, 3,4 achieving trapped magnetic fields up to 7.34 T at 4.2 K in the middle point between two 12 mm square stacks, each made of 120 layers of 2G-HTS tapes. This surprisingly high value for the trapped magnetic field given the small size of the stack together with the commercial availability of the tapes, almost uniform physical properties in long lengths, and considerably higher mechanical strength compared with the one of superconducting bulks, 4 makes the stack configuration of 2G-HTS tapes an ideal candidate for practical applications where strong magnets are required.…”
mentioning
confidence: 99%